The Right To Work in Article 27 Of The Un-Convention On The Rights of Persons With Disabilities: Towards An Inclusive Employment - Yeni Rosdianti (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2018)
Work is essential for every human being, not only in economic meaning, but also in the sense of dignity. It guarantees to sustain life and also a tool of inclusion as a vital social relationship in a society. Dignity outlines the principle of equality to form an inclusive society. Thereunto, a social inclusion is an objective whereby disadvantaged groups are fully respected yet enjoying their maximum equal participation in the society. Social inclusion is the ultimate goal of disability movements. In this respect, human rights play its crucial roles to acknowledge the rights of persons with disabilities which centered on an equality and non-discrimination principles. United Nation Convention on the Rights of Persons with Disabilities (hereinafter CRPD), that has been ratified by Indonesian Government in 2011, draws the enormous attention specifically on the protection of the persons with disabilities within a broad application of general human rights norms. This treaty is considered as a modern human rights model of disability. With respect to work and employment for persons with disability, article 27 elucidates a development of the right to work of persons with disabilities to aim an inclusive employment. For this reasons, CRPD acknowledges the positive measures to be applied as the vigorous means in removing structural barriers to date. Abstrak“Bekerja” memegang peranan penting dalam kehidupan umat manusia, tidak hanya dalam arti ekonomi namun juga bermakna pemuliaan martabat manusia. Bekerja, selain dapat menjamin penghidupan, juga merupakan alat pencapaian inklusi dan partisipasi setara dalam relasi sosial. Martabat manusia menjadi landasan prinsip kesetaraan untuk membentuk masyarakat inklusif dimana kelompok rentan secara penuh dihormati hak-haknya hingga dapat berpartisipasi secara maksimal di tengah-tengah masyarakat. Hak Asasi Manusia (HAM) memegang peranan penting dalam hal ini, khususnya terkait dengan pemajuan hak-hak penyandang disabilitas dalam kerangka prinsip-prinsip kesetaraan dan non-diskriminasi. Konvensi Persatuan Bangsa-Bangsa tentang Hak-hak Penyandang Disabilitas (Atau selanjutnya disebut CRPD) yang telah diratifikasi oleh Pemerintah Indonesia pada tahun 2011, meletakkan dasar yang kokoh bagi perlindungan hak-hak penyandang disabilitas dalam penerapan kaidah-kaidah dasar HAM. Konvensi ini dianggap sebagai model disabilitas terkini yang mengacu pada pendekatan HAM. Terkait dengan hak atas pekerjaan khususnya untuk penyandang disabilitas, pasal 27 CRPD meletakkannya dalam rangka mencapai dunia kerja yang inklusif dan setara. Untuk itu, CRPD mendorong langkah-langkah positif (positive measures) sebagai sarana menyingkirkan hambatan struktural yang dihadapi oleh penyandang disabilitas selama ini.